AB1031 DYSKERATOTIC CELLS IN PERSISTENT PRURITIC SKIN LESIONS AS A PROGNOSTIC FACTOR IN ADULT-ONSET STILL'S DISEASE. (2nd June 2020) - Inotani, S.; Taniguchi, Y.; Nishikawa, H.; Maeda-Aoyama, N.; Nakajima, K.; Arii, K.; Terada, Y.
Abstract : Background: Adult-onset Still's disease (AOSD), a systemic inflammatory disorder, is characterized by high fever, evanescent rash, arthritis, and hyperferritinaemia. AOSD is also reported to be associated with other skin lesions, including persistent pruritic papules and plaques. Objectives: This study aimed to assess the significance of dyskeratotic skin lesions in Japanese AOSD patients. Methods: We retrospectively assessed the histology of persistent pruritic skin lesions and evanescent rashes and the relationship between dyskeratotic cells, serum markers, and outcomes in 20 Japanese AOSD patients, comparing AOSD histology with that of dermatomyositis (DM), drug eruptions, and graft-versus-host disease (GVHD). Results: Persistent pruritic lesions were characterized by scattered single keratinocytes with an apoptotic appearance confined to the upper layer of the epidermis and horny layer without inflammatory infiltrate. In contrast to AOSD, the histology of DM, drug eruption, and GVHD demonstrated dyskeratotic cells in all layers of the epidermis with inflammatory infiltrate. AOSD with evanescent rash showed no dyskeratotic cells. The dyskeratotic cells in pruritic AOSD lesions stained positive for ssDNA and terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling, indicating apoptosis. Serum IL-18 was significantly higher in AOSD patients with dyskeratotic cells than those without, and generally required higher doses of glucocorticoids, immunosuppressants, and biologic agents. Two of ten AOSD patients with dyskeratotic cells died from haemophagocytic lymphohistiocytosis. Conclusion: Persistent pruritic AOSD skin lesions are characterized by dyskeratotic cells with apoptotic features, involving the upper layers of the epidermis. There may be a link to elevated IL-18. This dyskeratosis may be a negative prognostic indicator. Disclosure of Interests: None declared